2016
DOI: 10.1371/journal.pone.0150821
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Randomized Placebo Controlled Trial of Electroacupuncture for Women with Pure Stress Urinary Incontinence

Abstract: BackgroundAcupuncture is a potential conservative therapy for women with stress urinary incontinence (SUI). There is limited evidence to support its effectiveness due to the poor quality of existing studies.MethodsWe performed a pilot randomized, controlled trial to preliminarily assess the efficacy of electroacupuncture (EA) in women with pure SUI. A total of 80 women with pure SUI were randomly assigned to receive EA with deep needling at BL33 and BL35 (n = 40) or sham EA with non-penetrating needling at sha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 38 publications
2
20
0
2
Order By: Relevance
“…Our results are in agreement with the findings of a previous pilot randomised controlled trial treating general female SUI patients with EA, 36 which showed that the change in the ICIQ-SF score from baseline ranged from 1.75 to 5.89. In summary, the results suggest that both groups were able to benefit from a 6-week EA treatment for improving UI symptoms, regardless of BMI category.…”
Section: International Consultation On Incontinence Questionnaire-shortsupporting
confidence: 92%
See 3 more Smart Citations
“…Our results are in agreement with the findings of a previous pilot randomised controlled trial treating general female SUI patients with EA, 36 which showed that the change in the ICIQ-SF score from baseline ranged from 1.75 to 5.89. In summary, the results suggest that both groups were able to benefit from a 6-week EA treatment for improving UI symptoms, regardless of BMI category.…”
Section: International Consultation On Incontinence Questionnaire-shortsupporting
confidence: 92%
“…The change in the ICIQ‐SF score from baseline to week 2 through week 36 in the obesity group ranged from 2.12 to 7.78, compared with 2.31‐7.41 in the non‐obesity group with a between‐difference of −0.49 to −0.03 (all P > .05). Our results are in agreement with the findings of a previous pilot randomised controlled trial treating general female SUI patients with EA, which showed that the change in the ICIQ‐SF score from baseline ranged from 1.75 to 5.89. In summary, the results suggest that both groups were able to benefit from a 6‐week EA treatment for improving UI symptoms, regardless of BMI category.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is essential to make sure whether electroacupuncture is a good option for the patients who are unable to have surgery, and whether it is as effective as other conservative or drug therapies. Studies have demonstrated that electroacupuncture can effectively reduce the symptoms of SUI, [ 16 , 20 ] but its efficacy has not been evaluated scientifically and systematically. We have developed a protocol of systematic evaluation to assess the effectiveness and safety of electroacupuncture treatment on women with SUI, and the process is shown in the flow diagram in Fig.…”
Section: Discussionmentioning
confidence: 99%